Работы М.Г. Крейна по проблеме моментов - Нудельман, А.А. (Український математичний журнал, 1994)
Наведено огляд праць М.Г. Крейна по пробемі моментів. This is a survey of М. G. Krein's papers devoted to the moment problem.